2011
DOI: 10.1111/j.1600-6143.2010.03338.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression with Belatacept-Based, Corticosteroid-Avoiding Regimens in De Novo Kidney Transplant Recipients

Abstract: †Drs Ferguson and Grinyo contributed equally to the work described.Current immunosuppressive regimens in renal transplantation typically include calcineurin inhibitors (CNIs) and corticosteroids, both of which have toxicities that can impair recipient and allograft health. This 1-year, randomized, controlled, open-label, exploratory study assessed two belatacept-based regimens compared to a tacrolimus (TAC)-based, steroidavoiding regimen. Recipients of living and deceased donor renal allografts were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
205
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(213 citation statements)
references
References 46 publications
7
205
0
1
Order By: Relevance
“…In addition, recent trials have demonstrated acceptable outcomes (with somewhat better long-term allograft function) for belataceptbased immunosuppressive regimens compared with calcineurin inhibitor-based therapy. 37,38 Trials designed to evaluate the efficacy of these and other calcineurin-sparing regimens could be planned in recipients identified as high risk for DGF based on urinary YKL-40 levels before or immediately after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent trials have demonstrated acceptable outcomes (with somewhat better long-term allograft function) for belataceptbased immunosuppressive regimens compared with calcineurin inhibitor-based therapy. 37,38 Trials designed to evaluate the efficacy of these and other calcineurin-sparing regimens could be planned in recipients identified as high risk for DGF based on urinary YKL-40 levels before or immediately after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Only four induction studies [71][72][73][74] and six maintenance studies 58,[124][125][126][127]150 adequately addressed five or more of the 10 items of the quality appraisal assessment. However, even the reports of these trials omitted important information relating to quality, with six [71][72][73][74]124,125 of the seven failing to clearly describe the procedure used for allocation concealment, and one 58 failing to include an intention-to-treat (ITT) analysis.…”
Section: Overall Assessmentmentioning
confidence: 99%
“…The method of random allocation, 71,86,128 including the method of sequence generation, was clearly stated and adequate in only two induction studies 71,128 and 18 maintenance studies, 86,103,110,112,119,122,124,126,127,[129][130][131][132][133][134][135][136]150 whereas 65 studies (nine induction studies [72][73][74]87,95,98,137 and 54 maintenance studies 51,58,59,75-85,88,89,91-94,99-102, 104-109,111,113-118,120,121,125,138-147,152-155 ) and both of the studies of induction and maintenance treatment 123,148 did not clearly specify the method used. The remaining maintenance study 149 used a minimisation technique that included a random element.…”
Section: Random Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…After a 12 months study the biopsy proven AR rate for belatacept/MMF was 14%; for belatacept/sirolimus this fi gure was 4% and for control TAC/MMF this incidence was 3%. Steroid-free immunosuppression may, therefore, not be achieved through CNI-free protocols [61][62][63].…”
Section: Novel Immunotherapy and Steroid Avoidancementioning
confidence: 99%